Synthetic studies toward tricyclic cembranoids: a modular approach for the construction of the tricyclic framework of eunicin - Gurjar, MK; Nayak, S; Ramana, CV (Tetrahedron Letters, 2005)
The synthesis of a sugar derived allene and its intramolecular silver mediated etherification followed by ring closing metathesis has been explored for building the tricyclic framework of eunicin. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: Allene; Carbohydrate; cembranoid; eunicin; Ring closing metathesis